Nephrectomy in a Dog infected with Dioctophyma renale - Mato Grosso do Sul, Brazil - Santos, Mariana Ramos; do Nascimento, Camila Baloque; Favacho, Júlia de Mendonça; dos Santos, Camila Maria; Suzukawa, Miwa Fabiane; Favacho, Alexsandra Rodrigues de Mendonça (Acta Scientiae Veterinariae, 2022)
Background: Dioctophymosis is caused by Dioctophyma renale, a parasite known as the giant kidney worm, that can parasitize the kidneys of domestic and wild animals. There are also reports of its occurrence in humans, thus revealing its zoonotic potential. In most cases, parasitized animals are asymptomatic. This parasite can cause atrophy or destroy the renal parenchyma, although ectopic locations may occur. The diagnosis is made through ultrasonography, based on the presence of eggs in the urine, visualization of the parasite, or during necropsy. Therefore, the aim of this work was to report the case of a young dog infected with D. renale and subjected to nephrectomy in the state of Mato Grosso do Sul, Brazil. Case: A 6-month-old bitch with a clinical suspicion of hydronephrosis in the right kidney was referred to the Veterinary Hospital of Anhanguera-Uniderp University in the city of Campo Grande, MS. A physical examination of the patient revealed an alteration in the urinary system. An abdominal ultrasound, urinalysis, complete blood count (CBC) tests and biochemical profile were ordered. The erythrogram indicated erythrocytosis resulting from dehydration and loss of body fluids, while enzyme levels (creatinine, urea, alanine aminotransferase [ALT] and albumin) were within normal limits. The abdominal ultrasound showed the presence of a cylindrical and rounded structure characteristic of a nematode and in the right kidney, and loss of renal parenchyma typical of D. renale infection. A urinalysis then revealed the presence of helminth eggs, confirming the diagnosis. The owner was informed about the need for nephrectomy of the affected right kidney, which showed destruction of the renal parenchyma. One adult female and one adult male parasite were removed from inside the kidney, measuring approximately 50 cm and 35 cm in length. The patient was successfully treated, kept in hospital for observation, and returned two weeks later for reassessment of her renal function and removal of stitches. Discussion: Dioctophymosis is often diagnosed based on ultrasound and urine tests. These tests proved sufficient to diagnose parasitism by D. renale. However, the infection is usually discovered during necropsy. D. renale is popularly known as the giant kidney worm, as it can reach up to 100 cm in length. In the present case, the female parasite was 50 cm long and the male was 35 cm. The patient presented parasitism very young, at just 6 months of age. The parasitic infection of the animal was attributed to the ingestion of water or food contaminated with an intermediate host, the aquatic annelid Lumbriculus variegatus. It is suggested that the ingestion of food or water contaminated with the infective stage of the parasite may have occurred at 2 months of age or younger, since the prepatent period is approximately 6 months. The parasite was found only in the patient’s right kidney. Hydronephrosis was reported in the patient and was caused by obstruction of the internal urethral ostium by the adult nematode. In this case, the recommended surgical treatment was nephrectomy, to which the patient was subjected, leading to successful recovery. This case occurred in the state of Mato Grosso do Sul, where there are no records of parasitism by D. renale in domestic dogs, unlike other states in Brazil. We therefore emphasize the importance of new studies on D. renale, given the lack of clear records describing the parasite’s epidemiological data, biological cycle and diagnosis, which may hinder the prevention and control of this zoonotic disease. Keywords: canine dioctophymosis, helminth, nematoid, giant kidney worm, hydronephrosis. Descritores: dioctofimose canina, helminto, nematoide, verme gigante renal, hidronefrose.